2017
DOI: 10.3390/foods6060043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sweet Potato Starch-Based Nanocomposite Films Activated With Thyme Essential Oil on the Shelf-Life of Baby Spinach Leaves

Abstract: Salmonella Typhimurium (S. Typhi) and Escherichia coli (E. coli) have been responsible for an increasing number of outbreaks linked to fresh produce, such as baby spinach leaves, in the last two decades. More recently, antimicrobial biodegradable packaging systems have been attracting much attention in the food packaging industry as eco-friendly alternatives to conventional plastic packaging. The objective of this study was to evaluate the effect of antibacterial nanocomposite films on inoculated spinach leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 36 publications
3
30
0
1
Order By: Relevance
“…In fact, SPS-based coatings containing 6% TEO exhibited higher bactericidal or bacteriostatic activity compared to 2% or 4% TEO. The findings in this study are in agreement with those of Issa et al [5], who highlighted that 6% TEO exhibited potent antibacterial activity against major food-borne microbes. The present study further showed that the synergistic antibacterial activity of SPS and TEO was evident with 4% and 6% TEO.…”
Section: Antibacterial Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, SPS-based coatings containing 6% TEO exhibited higher bactericidal or bacteriostatic activity compared to 2% or 4% TEO. The findings in this study are in agreement with those of Issa et al [5], who highlighted that 6% TEO exhibited potent antibacterial activity against major food-borne microbes. The present study further showed that the synergistic antibacterial activity of SPS and TEO was evident with 4% and 6% TEO.…”
Section: Antibacterial Analysissupporting
confidence: 93%
“…The terpenoids are active against a broad spectrum of microorganisms. The antimicrobial action of phenolic compounds, such as thymol and carvacrol, is expected to cause structural and functional damages to the cytoplasmic membrane [5].…”
Section: Antibacterial Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Biodegradable films were obtained by the casting method, in agreement with the methodology proposed by Issa and his collaborators, 17 with some modifications. In order to obtain films, 5 g commercial arrowroot starch was dissolved in 100 mL distilled water; the mixture was moderately agitated at room temperature (25 °C).…”
Section: Development Of Biodegradable Filmssupporting
confidence: 67%
“…Active packaging that incorporates natural antimicrobial agents has attracted more attention as a replacement for synthetic agents in the food packaging industry. In our previous study, thyme ( Thymus vulgaris ) essential oil exhibited strong antibacterial and antioxidant activities . Therefore, the incorporation of nanoclays and natural antimicrobials into biopolymer films makes them comparable to conventional synthetic films with the advantages that they reduce environmental pollution and food safety issues.…”
Section: Introductionmentioning
confidence: 99%